2021
DOI: 10.1007/s00436-021-07323-4
|View full text |Cite
|
Sign up to set email alerts
|

The return of chloroquine-sensitive Plasmodium falciparum parasites in Jazan region, southwestern Saudi Arabia over a decade after the adoption of artemisinin-based combination therapy: analysis of genetic mutations in the pfcrt gene

Abstract: This study investigated the polymorphism in the P. falciparum chloroquine resistance transporter (pfcrt) gene 11 years after chloroquine (CQ) cessation in Jazan region, southwestern Saudi Arabia. Two hundred and thirty-ve P. falciparum isolates were ampli ed to detect mutations in the pfcrt gene. The pfcrt 76T molecular marker for CQ resistance was detected in 66.4% (156/235) of the isolates, while the K76 CQ-sensitive wild type was detected in 33.6%. The pfcrt 74I and pfcrt 75E point mutations were each found… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 58 publications
2
5
0
Order By: Relevance
“…In contrast, a high prevalence of Pfcrt K76 T (67.5%) and Pfmdr 1 N86 Y (80%) was observed in another study conducted before CQ withdrawal from the state during 2008–2010 [ 17 ]. The result obtained is similar to the observations made in Malawi, Tanzania, Mozambique, Northern Uganda, Saudi Arabia [ 23 27 ], but in contrast to southern Benin [ 28 ] and in other parts of India reported recently [ 29 32 ]. The present study, although limited to a small number of samples, indicates not only the presence of three types haplotypes (CVMNK: wild type, CV IET mutant type: believed to be of Southeast Asian origin, CVMN T mutant type: believed to be of African Origin) but also inform the high genetic diversity present in field isolates of P. falciparum for CQ drug-resistant genes in Odisha, India.…”
Section: Discussionsupporting
confidence: 90%
“…In contrast, a high prevalence of Pfcrt K76 T (67.5%) and Pfmdr 1 N86 Y (80%) was observed in another study conducted before CQ withdrawal from the state during 2008–2010 [ 17 ]. The result obtained is similar to the observations made in Malawi, Tanzania, Mozambique, Northern Uganda, Saudi Arabia [ 23 27 ], but in contrast to southern Benin [ 28 ] and in other parts of India reported recently [ 29 32 ]. The present study, although limited to a small number of samples, indicates not only the presence of three types haplotypes (CVMNK: wild type, CV IET mutant type: believed to be of Southeast Asian origin, CVMN T mutant type: believed to be of African Origin) but also inform the high genetic diversity present in field isolates of P. falciparum for CQ drug-resistant genes in Odisha, India.…”
Section: Discussionsupporting
confidence: 90%
“…Interestingly high rates of wild alleles of Pfcrt (K76, 98%) and Pfmdr1 (N86 and Y184, 97%) observed in this study compared to our earlier study conducted before CQ withdrawal during 2008-2010 [15] provides evidence of the return of CQ-susceptible P. falciparum strains in Odisha. The results obtained is similar to the observations made in Malawi, Tanzania, Mozambique, Northern Uganda, Saudi Arabia [37,38,39,40,41] but in contrast to southern Benin [30]. Further DNA sequence polymorphism study that not only informs distribution of different haplotypes, but also the evolutionary potentiality of mutation in the drug-resistant genes that can directly translate to molecular epidemiology of human diseases like malaria.…”
Section: Discussionsupporting
confidence: 85%
“…Also, a study found that the initial response of C-SP was significantly better than that of AL ( Mayxay et al, 2003 ). However, due to the emergence of recurrent resistance to Plasmodium falciparum, some areas had to stop using chloroquine and sulfadiazine as antimalarial drugs ( Mekonnen et al, 2014 ; Madkhali et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%